Looking at Legal Regulation in Handling the Issues of Online Gender-Based Violence - Fadhilah Aini; Zulfa Ajda Khoiriyah; Yogi Yoga Swara (Methods in Science and Technology Studies, 2025)
The development of information and communication technology has changed the way of social interaction, especially among Generation Z. The increasing use of the internet in Indonesia, which will reach 79.5% in 2024, brings new challenges in the form of Online Gender-Based Violence (OGBV). This study aims to explore the condition of legal education related to OGBV and efforts to prevent and handle it. This study uses a qualitative approach with a descriptive study method. Data were collected through random sampling among Generation Z, by combining primary and secondary data from various sources such as books, articles, and reports. The analysis was conducted to describe the actual condition of legal education in the context of OGBV. The findings show that despite increased legal awareness and regulations in the law related to OGBV, cases of this violence are still increasing. Data from the National Commission on Violence Against Women shows a spike in reports of OGBV cases from 16 complaints in 2017 to 1,272 in 2023. The most common type of violence is the threat of spreading sexual content. Although regulations have been in place, their effectiveness in preventing OGBV is still questionable. This study emphasizes the importance of socialization and increasing legal understanding among individuals to address the issue of OGBV more effectively. Legal culture reform and community engagement are needed to create a safer environment for internet users.